Children, risk and safety on the Internet research and policy challenges in comparative perspective - Livingstone, Sonia M. 1960-; Haddon, Leslie 1956-; Görzig, Anke 1974- (Policy, 2012)
Based on an impressive in-depth survey of 25,000 children carried out by the EU Kids Online network, this timely book examines the prospect for young internet users of enhanced opportunities for learning, creativity and communication set against the fear of cyberbullying, pornography and invaded privacy